2021
DOI: 10.3390/foods10122954
|View full text |Cite
|
Sign up to set email alerts
|

Control of Foodborne Staphylococcus aureus by Shikonin, a Natural Extract

Abstract: Foodborne Staphylococcus aureus (S. aureus) has attracted widespread attention due to its foodborne infection and food poisoning in human. Shikonin exhibits antibacterial activity against a variety of microorganisms, but there are few studies on its antibacterial activity against S. aureus. This study aims to explore the antibacterial activity and mechanism of shikonin against foodborne S. aureus. The results show that the minimum inhibitory concentrations (MICs) and the minimum bactericidal concentrations (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…The results of this study are consistent with the above results, confirming that juglone has antibacterial activity against S. aureus . This antibacterial activity may be related to the naphthoquinone structure of juglone, as our previous study showed that shikonin has good anti- S. aureus activity because it has a naphthoquinone structure [ 17 ]. As another example, plumbagin has better antibacterial activity against methicillin-resistant Staphylococcus aureus [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are consistent with the above results, confirming that juglone has antibacterial activity against S. aureus . This antibacterial activity may be related to the naphthoquinone structure of juglone, as our previous study showed that shikonin has good anti- S. aureus activity because it has a naphthoquinone structure [ 17 ]. As another example, plumbagin has better antibacterial activity against methicillin-resistant Staphylococcus aureus [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the antibacterial activity of shikonin was studied against S. aureus ATCC 29213 strain, and the results were correlated with the intracellular ATP concentration, reflecting the integrity of the bacterial cell membrane. 52 Compared with the untreated group, the intracellular ATP concentration of the shikonin-treated group was significantly decreased, indicating cell membrane damage on shikonin treatment (Figure 4). Besides, the target strain and the source and purity of shikonin may also lead to variation in the results.…”
Section: Antibacterial Activitymentioning
confidence: 93%
“…In another similar study involving a different test method, MIC of 125 μg/ml was also observed against S. aureus . In a recent study, the antibacterial activity of shikonin was studied against S. aureus ATCC 29213 strain, and the results were correlated with the intracellular ATP concentration, reflecting the integrity of the bacterial cell membrane 52 . Compared with the untreated group, the intracellular ATP concentration of the shikonin‐treated group was significantly decreased, indicating cell membrane damage on shikonin treatment (Figure 4).…”
Section: Important Properties and Related Applications Of Shikoninmentioning
confidence: 94%
See 2 more Smart Citations